Embedded dual switched-capacitor based continuous input current switched-inverter for renewable energy application - Ahmad A.; Singh R.K. (My University, 2025)
This study presents a high voltage gain embedded dual switched-capacitor-based continuous input current impedance source inverter for renewable energy applications. Renewable energy resources have low-output voltage generation capability, and the converter needs to operate on the extreme duty cycle for high voltage requirements. To achieve high voltage gain, a conventional impedance source inverter needs to operate on a high duty cycle, which leads to the reduction in modulation index. Operating at a reduced value of modulation index leads to poor inversion operation with poor output power quality. In order to take care of this issue, an embedded dual switched-capacitor-based inverter is presented for high voltage gain in low shoot-through duty cycle. The proposed inverter is suitable for DC–AC power conversions such as solar photovoltaic where a low-input voltage is available, and it needs to be converted into high DC–AC output voltages. Anatomisation of operating principle, steady-state analysis, passive design criteria, and comparison are discussed. The proposed inverter also has less capacitor voltage stress, less diode current stress, and higher efficiency than other impedance-source inverters. The operation of the proposed inverter is verified through simulations and experimental results with a 600W prototype. © The Institution of Engineering and Technology 2019.